REPRESENTASI PELANGGARAN HAK ASASI MANUSIA DALAM FILM “DE OOST/THE EAST” (Analisis Semiotik Charles Sanders Peirce) - Rabani, Olgheri Paco Syah; Suryawati, I Gusti Agung Alit; Joni, I Dewa Ayu Sugiarica; Damasemil, Calvin (E-Jurnal Medium, 2023)
As one of the mass communication media, film acts as a medium for delivering messages to audiences through audio and visual. “De Oost/The East” is a film that depicts violence during the Indonesian war of independence. This study aims to see the representation of human rights violations in the film